CONTRIBUTION TO THE KNOWLEDGE OF THE FAUNA OF CYNIPID GALL WASPS ON THE TERRITORY OF BELGRADE (SERBIA) (Acta Entomologica Serbica, 2017)
In studying the fauna of cynipid gall wasps of Belgrade and its environs during the period from 1997 to 2016, we recorded a total of 46 species from four tribes (Aylacini, Cynipini, Diastrophini and Diplolepidini) and 12 genera (Andricus, 27 species; Diplolepis, 5 species; Cynips, 3 species; Neuroterus, 3 species; Diastrophus, 2 species; Aphelonyx, 1 species; Barbotinia, 1 species; Biorhiza, 1 species; Callirhytis, 1 species; Chilaspis, 1 species; Dryocosmus, 1 species; and Pseudoneuroterus, 1 species). The following species are here recorded as new for the Serbian fauna of cynipid gall wasps: Diastrophus mayri Reinhard,1876; D. rubi (Bouche, 1834); Andricus aries (Giraud, 1859); A. conificus (Hartig, 1834); A. gallaeurnaeformis (Boyer de Fonscolombe, 1832); A. grossulariae Giraud, 1859; A. inflator Hartig, 1840; A. superfetationis (Giraud, 1859); Callirhytis glandium (Giraud, 1859); and Chilaspis nitida (Giraud, 1859). For all the recorded species, we give the localities, dates and hosts on which they were found in Belgrade and its environs.